2021
DOI: 10.1101/2021.10.31.466701
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protective and aggressive bacterial subsets and metabolites modify hepatobiliary inflammation and fibrosis in PSC

Abstract: ObjectiveConflicting microbiota data exist for primary sclerosing cholangitis (PSC) and experimental models. Goal: Define complex interactions between resident microbes and their association in PSC patients by studying antibiotic-treated specific pathogen-free (SPF) and germ-free (GF) multi-drug-resistant 2 deficient (mdr2-/-) mice.DesignWe measured weights, liver enzymes, RNA expression, histological, immunohistochemical and fibrotic biochemical parameters, fecal 16s rRNA gene profiling, and metabolomic endpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…In addition this study Zhu et al 10.3389/fmicb.2024.1342356 Frontiers in Microbiology 16 frontiersin.org also revealed that the abundance of Oscillibacter (also a SCFAproducing bacterium) is markedly reduced accompanied by a notable decrease in the ratio of Firmicutes and Bacteroidetes along with the progression from compensated cirrhosis to decompensated cirrhosis. Further the SCFA-producing Lachnospiraceae family can reduce liver fibrosis and the SCFA-producing families (Ruminococcaceae and Lachnospiraceae) may have a potential association with the progression of HE in cirrhotic patients (Awoniyi et al, 2023). Supplementation with probiotics targeting to enhance the population of SCFA-producing bacteria emerges as a potential therapeutic strategy for cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition this study Zhu et al 10.3389/fmicb.2024.1342356 Frontiers in Microbiology 16 frontiersin.org also revealed that the abundance of Oscillibacter (also a SCFAproducing bacterium) is markedly reduced accompanied by a notable decrease in the ratio of Firmicutes and Bacteroidetes along with the progression from compensated cirrhosis to decompensated cirrhosis. Further the SCFA-producing Lachnospiraceae family can reduce liver fibrosis and the SCFA-producing families (Ruminococcaceae and Lachnospiraceae) may have a potential association with the progression of HE in cirrhotic patients (Awoniyi et al, 2023). Supplementation with probiotics targeting to enhance the population of SCFA-producing bacteria emerges as a potential therapeutic strategy for cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…An experiment on a PSC mouse model showed that the reduction of bacteria weakened the negative feedback regulation of BAs and then enhanced the accumulation of BAs in the liver. The decrease in bacteria also altered the composition of BAs (Schneider et al, 2021;Awoniyi et al, 2023). In addition, studies have shown that intestinal microbiota dysfunction plays an important role in the progression of PSC (Jin et al, 2022).…”
Section: Non-calculous Cholangitis and Intestinal Microbiotamentioning
confidence: 97%